THE EVALUATION OF ENGLISH FOR GENERAL ACADEMIC PURPOSES (EGAP) COURSE IN AN INDONESIAN UNIVERSITY - Flora Debora Floris (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
This  paper  presents  an  internal  evaluation  on  English  for  General Academic Purposes (EGAP) subject which is developed by the English Language Teaching  Center  (ELTC)  from  a private  university  in East  Java,  Indonesia.  The research  was  conducted  to  elicit  feedback  on  the  effectiveness  of  English  for General Academic Purposes (EGAP). The presented data were obtained from questionnaires,  group  interviews,  classroom  observations  and  the  students’  final scores. There were 124 students and 6 lecturers involved in this small-scale research. Therefore, this paper is intended to describe the interesting facts of the study.